ANALISIS KESULITAN GURU DALAM MELAKUKAN PENILAIAN MATA PELAJARAN MATEMATIKA SELAMA PEMBELAJARAN DARING DI SMP NEGERI 5 ANGKOLA TIMUR - Siregar, Sri Puspa; Harahap, Muhammad Syahril; Lubis, Roslian (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
Abstract This study aims to know the description of the teacher's difficulties in assessing knowledge (cognitive), assessing attitudes (affective) and assessing skills (psychometrics) in mathematics subjects during online learning at SMP Negeri 5 Angkola Timur. The research used qualitative method and the object of research is the difficulty of teachers assessing mathematics subjects during online learning. The researcher determined that the informants included three mathematics teachers at SMP Negeri 5 Angkola Timur. Data collection techniques used observation, questionnaires, interviews, and documentation. The data validity technique used triangulation. Data analysis techniques consist of data reduction, data presentation and conclusion drawing. The results of research show the questionnaire describes the aspect of knowledge (cognitive) assessment is 75 (difficult category), the attitude assessment obtained is 78.33 (difficult category), and d the skill assessment (psychometric) obtained is 80.00 (very difficult category).